Anal Canal Duplication Mimicking Recurrent Abscess: A Case Report and Review of the Literature - Li, Dandan; Liu, Shuaibin; Feng, Jiexiong; Yang, Jixin (Frontiers in Surgery, 2022)
Background: Anal canal duplication (ACD) is a very rare duplication of the gastrointestinal tract and described as a secondary anal orifice along the posterior side of the normal anal canal. Surgical early removal is advisable, also in asymptomatic patients, because of the risk of inflammatory complications, such as recurrent crissum abscess, and malignant changes. Case presentation: A previously healthy 2-year-old boy was evaluated in the emergency department with fever and complained of anal pain in the absence of incentive. Physical examination and ultrasound confirmed a diagnosis of perianal abscess. He was treated with incision and drainage of the abscess and intravenous antibiotics. Two months after his discharge from the hospital, he developed fever and had intervals discharge pus and pain in the same locations. Colorectal endoscopy revealed that there was no fistula opening at the rectal wall. Intraoperative fistulography showed a fistulous tract was connected to a subcutaneous cavity. Excision of the fistulous tract and wide drainage of the deep postanal space was performed. The patient was referred to our hospital for further evaluation six months later. Physical examination showed a secondary anus which had not been noticed before. MRI showed an anal fistula between 1 and 3 o’clock and preoperative fistulography revealed a 3-cm-long tubular structure without connection with the rectum. The diagnose of ACD was made by intraoperative examination with a metal catheter and the postoperative pathological analysis. The duplicated anal canal was resected completely via perianal approach without rectal injury. Histology showed squamous epithelium in the distal end with some smooth-muscle fibers. Follow-up for eight months, the patient has been doing well. Conclusion：Recurrent crissum abscess should raise clinical attention to the alimentary tract congenital malformations, such as ACD. Prompt recognition of these unique presentations of ACD is needed and complete excision through a perineal approach or posterior sagittal approach is recommended.